Worldwide Survey of Clinician Practice on use of Adjunctive Therapies Following Botulinum Toxin Injection for Spasticity - Fabienne Schillebeeckx; Patricia B. Mills; Alvin Ip; Michal Schinwelski; Joao Eduardo Marten Teixeira; Stephen Ashford; Nicolas Bayle; Elena Chemello; Jorge Jacinto; Meenakshi Nayar; Erika Suzigan; Thierry Deltombe (Medical Journals Sweden, 2022)
Objective: Non-pharmacological adjunctive therapies can be used alongside botulinum toxin injection to enhance its efficacy. The objective of this global study was to determine the current practice and perception among clinicians of the use of adjunctive therapies after botulinum toxin injections for the treatment of limb spasticity. Methods: A questionnaire with 22 questions on clinical practice demographics, self-reported use and clinician opinion on barriers to the use of complementary therapies, and priorities for future research was translated into 7 languages and distributed worldwide through national and international professional associations concerning (neuro)rehabilitation. Results: A total of 527 clinicians from 52 countries responded to the survey. Most commonly used physical interventions were: active exercise programmes at home (81%), stretching programmes at home (81%), and splinting (70%), followed by active movement exercises (65%) and within 30 min of botulinum toxin injection and constraint induced movement therapy (63%). The main barriers reported by clinicians to provision of these interventions were clinicians' lack of time, limited financial resources, and lack of evidence. Future research should focus primarily on immediate active movement exercises and passive stretching. Conclusion: Worldwide, clinicians often recommend adjunctive therapies after a botulinum toxin injection to reduce spasticity. The most commonly used physical interventions among clinicians were active exercises at home, stretching at home, and splinting. Lack of evidence, time and financial constraints were identified as barriers to providing these interventions. LAY ABSTRACT A neurological injury, such as a stroke, traumatic brain injury or spinal cord injury, may cause muscle stiffness, a condition known as spasticity. Among available treatments for spasticity, botulinum toxin, a neurotoxin injected into the muscle, is used in cases of focal spasticity. Adjunctive therapies are therapies other than drugs that are used to enhance the efficacy of a treatment, such as botulinum toxin. The aim of this worldwide survey of clinicians was to determine the current clinical practice and perception of the use of adjunctive therapies following botulinum toxin injections. The results showed that the most frequently prescribed adjunctive therapies were active exercises at home, stretching at home, and splinting. The main barriers reported by clinicians to provision of these interventions were clinicians' lack of time, limited financial resources, and lack of evidence.